O artesão da “Feira do Largo da Ordem”: quem é esse trabalhador? - Bernardelli, Julio Cezar (2019)
This work aims to describe the craftsman as well as the meanings he attributed to craftsmanship. As specific objectives the research questioning addresses: What is the meaning of the work of the curitiban artisan? What is the influence of technology on your work process? What is your future career planning? To know the artisan, his origin and his way of working, the researcher had as reference the field of Science Technology and Society (STS) and the theoretical referential of historical and dialectical materialism. This is a qualitative methodological research in which were interviewed 06 artisans and 07 artisans who exhibit their work in the Largo da Ordem Fair, of both sexes were interviewed, who also recorded through photographs the influence of technology in their production process. Both the interviews and the photographs were submitted to the content analysis procedure. As a result the sense of artisan's work can be affirmed by tradition, personal fulfillment and family values. Despite the difficulties encountered by craftsmen to survive, there are countless gratifications that keep them engaged in their work. The influence of technology on its work process has little visibility or use in its daily making, being used only to perform repetitive tasks and great care is taken so that this technology does not affect the essence of the craft. The future planned or not is to keep connected with their work, and regardless of any legal protection, intend to continue exposing their products at the fair. Despite the obvious need for survival through work, in the case of the artisan the issue of financial compensation is secondary, given that the vast majority of them feel privileged to be able to create from the development of the raw material their craft.